ANALISA KOMPONEN KIMIA KAYU SENGON (Albizia falcataria (L.) Fosberg) BERDASARKAN POSISI KETINGGIAN BATANG - Ramadhan, Andi Ferry; Wardenaar, Evi; Husni, Harnani (Universitas Tanjungpura, 2018)
Knowledge of the nature and chemical composition of a type of wood makes the utilization of such wood as industrial cultivators such as pulp and paper, rayon, fiberboard, cement board, wood durability and others can be considered. A type of wood can be recommended as a raw material, it is necessary to introduce the wood in order that the processing, utilization, and treatment can be appropriate and efficient. The aim of this research is to know the chemical variation of sengon wood (Albizia falcataria (L.) Fosberg) based on height of stem (base, middle, and tip) which include extractive, holocellulose, alpha cellulose, and lignin.The chemical research of Albizia falcataria (L.) Fosberg wood was done by sampling of Ambawang River area, Kubu Raya District. The test was conducted in the laboratory of Forest Product Technology Faculty of Forestry, Tanjungpura University, Pontianak using ASTM standard. The purpose of this research is to know chemical component of Albizia falcataria (L.) Fosberg wood. Wood chemical components observed include percentage of moisture content, holocellulose, cellulose, lignin, and extractive (alcohol benzene) at the height position of the stem. The results showed that the moisture content of this wood is 13.5389 %, holocellulose 77.84616 % Of Alpha cellulose 64.29624 % (including high category), hemicellulose 13.54992 %, lignin 21.10961% (including moderate percentage), and extractive substances (alcohol benzene) are 3.226568 % (including moderate percentage).Keywords: Albizia falcataria (L.) Fosberg, Water content, Cellulose, Extractive, Holocellulose, Lignin.